2003
DOI: 10.1290/1543-706x(2003)039<0089:cdapca>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

CELL DIFFERENTIATION AND p38MAPK CASCADE ARE INHIBITED IN HUMAN OSTEOBLASTS CULTURED IN A THREE-DIMENSIONAL CLINOSTAT

Abstract: A three-dimensional (3D) clinostat is a device for multidirectional G force generation. By controlled rotation of two axes, a 3D clinostat cancels the cumulative gravity vector at the center of the device and produces an environment with an average of 10(-3) G over time. We cultured a human osteoblast cell line in a 3D clinostat and examined the growth properties and differentiation of the cells, including morphology, histological detection of calcification, and mitogen-activated protein kinase (MAPK) cascades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…In this study, we further demonstrated that SMG could enhance the multipotential differentiation capacity of BMSCs which enriches the previous studies. We used a clinostat for simulating microgravity, which could generate a multidirectional G force that placed the cells in a constant direction changing the gravity environment (Yuge et al 2003). As a result, the cells had no time to respond to normal gravity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we further demonstrated that SMG could enhance the multipotential differentiation capacity of BMSCs which enriches the previous studies. We used a clinostat for simulating microgravity, which could generate a multidirectional G force that placed the cells in a constant direction changing the gravity environment (Yuge et al 2003). As a result, the cells had no time to respond to normal gravity.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that p38 MAPK plays an important role in the differentiation of various cells, such as the adipocytic differentiation of 3T3L1 cells (Engelman et al, 1998), myogenic differentiation of C2C12 cells (Cuenda and Cohen, 1999), and neuronal differentiation (Morooka and Nishida, 1998;Iwasaki et al, 1999). Recently, the role of p38 MAPK in osteoblast differentiation has been reported (Suzuki et al, 2002;Yuge et al, 2003). Moreover, p38 MAPK and the Smad pathway play crucial roles in Runx2 expression following induction by transforming growth factor-beta and BMP (Lee et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have examined other human or animal cells under these conditions. Cell morphology changes were observed under weightlessness or simulated weightlessness in human osteoblast cells (Yuge et al, 2003) and erythrocytes from humans and rabbits (Shen et al, 1997). However, no significant changes have been observed for monkey kidney cells (Sato et al, 2001).…”
Section: Cellmentioning
confidence: 99%